Deteksi Dini Gangguan Tumbuh Kembang Anak di RA Darul Ihsan NW Toya - Haeriah, Haeriah; Aini, Baiq Halimatuz Zuhrotul; Turmuzi, H Ahmad; Ramdani, Zuhud; Irfan, Ahmad Zainul (Alpatih Harapan Semesta, 2025)
Early detection of developmental disorders in early childhood is a strategic step in supporting optimal child development. This study aims to describe the implementation of early detection of developmental disorders at RA Darul Ihsan NW Toya. This study used a descriptive qualitative approach with data collection techniques through observation and in-depth interviews with teachers, parents, and health centre staff. The results indicate that teachers have conducted structured observations in monitoring children's growth and development. However, parental participation remains limited and has not been optimally integrated. Collaboration with the health centre is carried out through health education and examinations, although it is not yet systematic. The conclusion of this study emphasizes the importance of collaboration between educational institutions, families, and health services. Practical implications include the need to enhance teachers' capacity, educate parents, and establish a sustainable cooperation system. It is recommended to develop a community-based early detection programme integrated into early childhood education.